2018
DOI: 10.1242/jeb.189001
|View full text |Cite
|
Sign up to set email alerts
|

ArHsp40 and ArHsp40-2 contribute to stress tolerance and longevity in Artemia franciscana, but only ArHsp40 influences diapause entry

Abstract: Embryos of the crustacean develop either ovoviviparously or oviparously, yielding swimming larvae (nauplii) or encysted gastrulae (cysts), respectively. Nauplii moult several times and become adults whereas cysts enter diapause, a state of dormancy characterized by exceptionally low metabolism and high stress tolerance. Synthesis of molecular chaperones such as the J-domain proteins ArHsp40 and ArHsp40-2 occurs during embryo development and post-diapause growth of and they influence development and stress tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Two J-domain proteins have been identified in Artemia: ArHsp40 and ArHsp40-2 (Jiang et al, 2016;Rowarth and MacRae, 2018b). Knockdown of either of the genes encoding these proteins reduces the percentage of cysts that are able to hatch following freezing and desiccation (Rowarth and MacRae, 2018a). Developmentally, ArHsp40 and ArHsp40-2 reach their peak expression levels in embryos exiting diapause (Jiang et al, 2016;Rowarth and MacRae, 2018b).…”
Section: Hsp70mentioning
confidence: 99%
“…Two J-domain proteins have been identified in Artemia: ArHsp40 and ArHsp40-2 (Jiang et al, 2016;Rowarth and MacRae, 2018b). Knockdown of either of the genes encoding these proteins reduces the percentage of cysts that are able to hatch following freezing and desiccation (Rowarth and MacRae, 2018a). Developmentally, ArHsp40 and ArHsp40-2 reach their peak expression levels in embryos exiting diapause (Jiang et al, 2016;Rowarth and MacRae, 2018b).…”
Section: Hsp70mentioning
confidence: 99%
“…The hatching percentage obtained was higher than those with their Hsp40 reduced by RNAi. Approximately 20 and 40% of cysts hatched, respectively, upon ArHsp40 and ArHsp40-2 knockdown (Rowarth and MacRae 2018). In another case, only 5 to 6% of cysts hatched upon p26 and group 1 LEA protein knockdown under the same experimental condition as used in this study (King and MacRae 2012;Toxopeus et al 2014).…”
Section: Resultsmentioning
confidence: 56%
“…These results showed that knockdown of Hsp70 had no apparent effect on the cyst morphology. Likewise, knockdown of a type 1 J-domain protein, ArHsp40, and type 2 J-domain protein, ArHsp40-2, had no apparent effect on brood size and time required to release cysts and nauplii in A. franciscana (Rowarth and MacRae 2018).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation